Entrepreneurship and Importance of Personality on Entrepreneurship: A Research on Trainees of Entrepreneurship Education Program - Develi, Evrim İldem; Erdil Şahin, Begüm; Sevimli, Yeliz (My University, 2011)
Enterprising personality has distinctive characteristics separating the entrepreneur from others. Therefore, the level of impact of personality and environmental factors on entrepreneurship has increasingly been discussed over the last years. Entrepreneur people are the ones which have ability to see the opportunities and seize, to take risks, to create innovation and implement. In this research, the notions of entrepreneur and entrepreneurship are defined, the important personal charactheristics of entrepreneur and the factors affecting entrepreneurship are explained and the relationship between these factors and the personality of entrepreneur are analyzed. Also, the effects of education and propose of developing business and entrepreneurial skills are mentioned. In this context, the research has been conducted on the trainees of the Applied Entrepreneurship Education Program, which has been organized with the collaboration of Istanbul Kültür University, KOSGEB (SME Development Organization) and İŞKUR (Turkish Job Foundation). The impact of personalities of the trainees on entrepreneurship have been evaluated within the study.
Keywords: Entrepreneur; Entrepreneurship; Personal Charactheristics of Entrepreneurs; Education